2019
DOI: 10.1002/cssc.201902565
|View full text |Cite
|
Sign up to set email alerts
|

Construction of 1T‐MoSe2/TiC@C Branch–Core Arrays as Advanced Anodes for Enhanced Sodium Ion Storage

Abstract: The use of active sites and reaction kinetics of MoSe2 anodes for sodium ion batteries (SIBs) are highly related to the phase components (1T and 2H phases) and electrode architecture. This study concerns the design and fabrication of wrinkled 1T‐MoSe2 nanoflakes anchored on highly conductive TiC@C nanorods to form 1T‐MoSe2/TiC@C branch–core arrays by a powerful chemical vapor deposition (CVD)–solvothermal method. The 1T‐MoSe2 branch can be easily transformed into its 2H‐MoSe2 counterpart after a facile anneali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…Thirdly, the Bi 2 Se 3 substrate provided superior surface electron transfer capability and donated alloying reaction to achieve high Na ions storage capacity upon cycling [45] . Fourthly, the broad interlayer spacing of MoSe 2 could accommodate the Na ions fast insertion/extraction processes [12] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirdly, the Bi 2 Se 3 substrate provided superior surface electron transfer capability and donated alloying reaction to achieve high Na ions storage capacity upon cycling [45] . Fourthly, the broad interlayer spacing of MoSe 2 could accommodate the Na ions fast insertion/extraction processes [12] …”
Section: Resultsmentioning
confidence: 99%
“…In general, TMDs have a large interlayer space to accommodate the Na ions insertion/ extraction and provide high additional capacity by participating in conversion reaction and alloying reaction, resulting in more attractive Na storage performance than carbonaceous materials. MoSe 2 , a classic two dimensional (2D) materials, is a promising material for SIBs due to the huge interlayer spacing (0.62 nm) and considerable theoretical capacity (422 mA h g −1 , based on 4 mol Li uptake into MoSe 2 per formula unit) [11,12] . Additionally, it has reported that MoSe 2 has better electronic conductivity than MoS 2 (1.557 eV for MoSe 2 vs. 1.856 eV for MoS 2 ), demonstrating the great potential of 2D MoSe 2 as SIB's anode [13] .…”
Section: Introductionmentioning
confidence: 99%
“…[ 11–15 ] Unlike semiconducting 2H‐MoSe 2 , 1T‐MoSe 2 exhibits metallic property with significantly enhanced electronic conductivity that brings about fast charge‐transfer kinetics. [ 16,17 ] Additionally, its octahedral structure featuring expanded interlayer spacing is more conducive to promoting Na + diffusion kinetics via lowing the diffusion energy barriers. [ 4 ] Furthermore, 1T phases are proved to have a better aptitude for inhibiting anion dissolution during conversion electrochemical reaction owing to their higher bond energies than 2H phases.…”
Section: Introductionmentioning
confidence: 99%
“…Ren et al [28] employed ultralight reduced graphene fiber fabrics as the skeleton to support SnS 2 nanosheets, forming binder-free composite electrodes of SIBs with improved electrochemical performance. In recent years, chemical vapor deposition (CVD)derived titanium carbide/carbon (TiC/C) nanowire arrays have been demonstrated as the ideal 3D conductive matrix for Li, [29] MnO 2 , [30] Ti 2 Nb 10 O 29, [31] and MoSe 2 [32] because of its unique properties such as high electrical conductivity, good mechanical strength, and outstanding resistance to chemical attack. Up to now, the research on combining TiC/C arrays with SnS 2 nanostructure has not been reported and its electrochemical performance as anode of SIBs is worthy of digging.…”
Section: Introductionmentioning
confidence: 99%